Global Health Clinical Ethics - Mei Elansary; Michael Peluso; Stacey Kallem; John Thomas; Tracy Rabin (Association of American Medical Colleges, 2015)
Abstract In recent years, increasing numbers of United States-based health professions students have traveled to low-resource settings for short-term clinical electives. The content of predeparture training can be highly variable, leaving students unprepared for the ethical challenges posed by these experiences. This is magnified by the lack of attention paid to the burdens and benefits for local staff, institutions, and patient well-being in the setting of disproportionate poverty and disease. Adequate predeparture training is necessary to help trainees recognize and navigate these ethical issues, avoid harm both to themselves and to others, and promote equitable global health partnerships. The case studies presented here, all of which are based on real student experiences, form the basis of this tool for predeparture training of health professions students preparing for international electives. The curriculum is designed to be implemented in a 90-minute session, in groups of up to 25 students. Student leaders, ideally a group of students who have had experience doing clinical rotations abroad, may serve as facilitators with faculty guidance. This module also includes evaluation tools to encourage continued curricular improvements. Analysis of the preworkshop, postworkshop, and posttrip questionnaires indicates that the students who engaged in these predeparture workshops demonstrated improved awareness of the range of ethical dilemmas that they might encounter while engaged in clinical work abroad, as well as increasing their self-rated ability to identify and negotiate these situations. Importantly, those students who participated in this workshop prior to travel felt more prepared to manage the ethical dilemmas that they encountered during their clinical rotations compared to those who did not participate.